Information services with cooperative methods to improve student's self autonomy - Cindy Marisa; Sri Utami (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The industrial revolution 4.0 requires creative, productive and competitive individuals. These personal criteria require the ability to be able to manage and make decisions independently to be accountable. Self-autonomy is the ability of individuals to regulate themselves so they are able to plan to evaluate the activities carried out appropriately. In adolescence, guidance and guidance is needed by an expert who is able to provide understanding, efforts to prevent negative conditions, and efforts to develop and maintain positive conditions related to self-autonomy. Information services are able to provide students with insight and knowledge related to autonomy, so students are able to utilize the information for their own development needs. Integrated with the cooperative method, in addition to being able to provide information indirectly it also trains students in developing their autonomy in group activities. In this study, we want to know the effectiveness and how much the contribution of information services with cooperative methods in increasing students' self-autonomy. We involved 11 students in this experiment. Based on the analyzed data, it proves that information services using the cooperative method are significantly effective in increasing student autonomy. So that it can be a reference for school counselors to be able to develop themselves students, especially in terms of self-autonomy. And also equip students to be ready to face the industrial revolution 4.0